Incidence of radiation proctitis in cervical cancer receiving radiation therapy at Dr. Kariadi Hospital, Semarang, Indonesia - Mirza Iskandar, Teuku; Kristiawan, Endy Cahyono; Faizal, Teuku Rendiza; Ambari, Ediwibowo; Putra, Very Great Eka; Achmad, Lubena (Universitas Airlangga, 2023)
HIGHLIGHTS Radiation proctitis is a post-radiotherapy concern, urging research to reduce its occurrence and improve the well-being of patients. Radiotherapy is the primary treatment for advanced cervical cancer, offering hope and preserving quality of life for patients. ABSTRACT Objective: To determine the incidence of radiation proctitis in cervical cancer patients after radiation at Dr. Kariadi Hospital, Semarang, Indonesia. Materials and Methods: A descriptive analytic study on 356 cervical cancer patients who received radiation therapy at Dr. Kariadi Hospital Semarang from January 2017 to December 2018 who met the inclusion criteria. Factors assessed included age, BMI, hematologic, stage, histopathology, history of radical hysterectomy surgery and duration of radiation. Cervical cancer staging was assessed using FIGO 2018. Statistical analysis was performed using Mann Whitney with a significant value of p <0.05. Results: From the Chi-square analysis, the relationship between radiation period (less than 56 days and more than 56 days) (p=0.164), the relationship between age ≥45 and the incidence of proctitis (p=0.208), BMI ≥25 and the incidence of proctitis (p=0.838), Hb <10 with the incidence of proctitis (p=0.492), parity ≤1 with the incidence of proctitis (p=0.137), the relationship between the histopathological examination results with the incidence of proctitis (p=0.253), and stage level with the incidence of proctitis (p=0.226) were not significant. The highest incidence of proctitis occurred in stage 3B of the cervical cancer patients (14.5%). Conclusion: The prevalence of proctitis in cervical cancer patients for the period 2017-2018 was 15.4%. Age, histopathological appearance, stage, history of anemia, history of radical surgery and appearance of symptoms after surgery with symptoms of proctitis did not show a significant relationship.